Elastic Carbon Nanotube Aerogel Meets Tellurium Nanowires: A Binder‐ and Collector‐Free Electrode for Li‐Te Batteries. (11th May 2016) - Xu, Jie; Xin, Sen; Liu, Jian‐Wei; Wang, Jin‐Long; Lei, Yong; Yu, Shu‐Hong
Abstract : Rechargeable Li batteries based on group VIA element cathodes, such as tellurium, are emerging due to their capability to provide equivalent theoretical volumetric capacity density to O and S, as well as an improved activity to react with Li. Herein, bifunctional and elastic carbon nanotube (CNT) aerogel is fabricated to combine with Te nanowires, yielding two types of binder/collector‐free Te cathodes to assemble Li‐Te batteries. The CNTs with high electronic conductivity and hollow porous structure enable stable electric contact and fast transportation of Li +, while trapping Te and Li2 Te in its network, triggering fast and stable Li‐Te electrochemistry. Both cathodes are also provided with fine compressibility, helping to buffer their volume changes during lithiation/delithiation and improving electrode integrity. Both cathodes deliver high specific capacity, fine cycling stability, and favorable high‐rate capability, proving their competence in building high‐energy rechargeable Li‐ion batteries. Abstract : Two types of binder/collector‐free Te cathodes (TeNW/CNT cathode and Te@CNT cathode) are constructed from a bifunctional and elastic carbon nanotube aerogel and Te nanowires, and are used for high‐energy Li‐Te batteries. The Te@CNT cathode exhibits excellent high‐rate stability in an extended cycling test at 1 C.